Gaya Bahasa dan Nilai-Nilai Pendidikan Karakter: Studi Stilistika-Kritik Sastra Heurmeneutika Terhadap Syair Da’il Ayyam - Idris, Ilham Maulana; Abdurohman, Maman (Institut Agama Islam Negeri Metro, 2025)
This study explores the uniqueness of the language style found in the classical Arabic poem Daʿ Il-Ayyām Tafʿal Mā Tashāʾ by Imam al-Shāfiʿī. Using an interdisciplinary approach that integrates stylistics and literary criticism, particularly Paul Ricoeur's hermeneutic theory, this study employs a descriptive-qualitative method. Documentation techniques are used as the main technique in data collection. 12 stanzas of the poem are analyzed at two main levels of stylistic analysis: syntax and morphology. Each linguistic level is examined based on its role in conveying the values ​​of character education in the poem. The research findings reveal that specific syntactic-morphological structures, such as the deliberate use of the imperative (fiʿl amr) 4 times and the prohibition forms (fi'il nahi) 2 times, the subjunctive form 1 time and the adjective form 2 times function as firm moral instructions and powerful means to express profound character values. The main character education values ​​revealed through stylistic analysis based on hermeneutic interpretation include the character education values ​​of tawakal (relief), patience, steadfastness, generosity, and maintaining honor. Overall, this study proves that the stylistic framework is an effective approach to uncovering the layered, implicit, and emotionally charged meanings in classical Arabic poetry, and underscores the importance of interdisciplinary analysis in bridging linguistic form and moral communicative function in literary discourse.